2020
DOI: 10.34133/2020/8378025
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Robot for Intraluminal Access: AnEx VivoFeasibility Study

Abstract: Early-stage gastrointestinal cancer is often treated by endoscopic submucosal dissection (ESD) using a flexible endoscope. Compared with conventional percutaneous surgery, ESD is much less invasive and provides a high quality of life for the patient because it does not require a skin incision, and the organ is preserved. However, the operator must be highly skilled because ESD requires using a flexible endoscope with energy devices, which have limited degrees of freedom. To facilitate easier manipulation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…One is inserted through a built-in channel of the standard endoscope and the other is inserted through an additional tube attached to the tip of the endoscope. The platform was originally developed as a mechanical system in which both endoscopes and instruments were controlled by a mechanically connected knob or handle [158] and then transformed to a fully motorized system where the endoscope and two instruments were remote controlled [149]. Ex vivo studies using a porcine stomach demonstrated that the platform allowed a novice to perform procedures more easily and quickly than conventional ESD [148], [149], [150].…”
Section: B) R-scopementioning
confidence: 99%
“…One is inserted through a built-in channel of the standard endoscope and the other is inserted through an additional tube attached to the tip of the endoscope. The platform was originally developed as a mechanical system in which both endoscopes and instruments were controlled by a mechanically connected knob or handle [158] and then transformed to a fully motorized system where the endoscope and two instruments were remote controlled [149]. Ex vivo studies using a porcine stomach demonstrated that the platform allowed a novice to perform procedures more easily and quickly than conventional ESD [148], [149], [150].…”
Section: B) R-scopementioning
confidence: 99%
“…Micromanipulations based on microrobots provide a variety of flexible and new methods for many biomedical studies, including functional cellular analysis, disease diagnosis and treatment, targeted drug delivery, and microsurgery monitoring [1][2][3]. There are an increasing number of studies on robots, especially microrobots, in the biomedical field [4][5][6][7][8]. Due to their small size, they cannot be powered by a built-in power supply, so they can only use external drive methods such as piezoelectric [9,10], optical [11], magnetic [12,13], acoustic [14][15][16], and electrical technologies [17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have developed multi-DOF endoluminal forceps with articulated joint structures [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. For instance, Anubiscope [5], STRAS [6], EndoMaster [7], and K-FLEX [8] have improved workability.…”
Section: Introductionmentioning
confidence: 99%
“…However, their diameters are not sufficiently small to be inserted into the 2.8 mm channel of commercially available prevailing standard flexible endoscopes. Other articulated devices [13][14][15][16][17][18][19] are within 2.6 mm in diameter. Thus, these devices might be used with standard flexible endoscopes even though each mechanism has its own limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation